Analisis Perbedaan Hasil Belajar Siswa Mengikuti Program Tahfidz Al-Qur’an (Studi Kasus di SMP Muhammadiyah 9 Watukebo Jember) - Sofyan Rofi (Universitas Muhammadiyah Jember, 2019)
Instructional systems on Tahfidz Al-Qur'an carried out at Muhammadiyah Secondary School 9 Watukebo are designed in line with activities of interest and talent. Students who take part in tahfidz Al-Qur'an at Watukebo Muhammadiyah 9 Secondary School are not limited to certain classes. The problem of this study was formulated as follows: what are the instructional systems applied in Tahfidz Al-Qur'an, and is there a difference in learning outcomes of students who take part in the Tahfidz Al-Qur'an program at Watukebo 9 Muhammadiyah Secondary School. This is a qualitative study, sources of data are selected by purposive sampling. Primary data sources are data that can be obtained directly from the observations and interviews while secondary data is obtained through documents. Informants in the study were the Tahfidz Al-Qur'an teacher and students who took part in the program. Data collection techniques included interviews and documentation. The validity of the data were examined through the triangulation technique. The conclusion of this study is that the isntructional systems of Tahfidz Al-Qur'an at Muhammadiyah Secondary School 9 Watukebo uses halaqah, the implementation of the program consists of three activities, namely periodic memorizing, sima'an and muroja'ah. The methods used included, for example, the talaqqi method, tasmi, takrir. The second conclusion: there are differences in students who take part in the Tahfiidz Al-Qur'an program at Muhammadiyah Secondary School 9 Watukebo, especially after they participated in the Tahfidz Al-quran program.